1998
DOI: 10.4315/0362-028x-61.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Populations of Listeria monocytogenes Inoculated on Packaged Fresh-Cut Vegetables

Abstract: A variety of wholesale and retail packaged vegetables and salads were inoculated with a mixture of strains of Listeria monocytogenes and incubated at 4 and 10 degrees C. Whole rutabagas, butternut squash, and onions, as well as packaged Caesar salad, carrots, coleslaw mix, and stir-fry vegetables were purchased from local supermarkets in the Ottawa area. L. monocytogenes population levels remained constant on all fresh-cut vegetables stored at 4 degrees C for 9 days, except for carrots and butternut squash: co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 0 publications
7
36
0
2
Order By: Relevance
“…Beuchat and Brackett (1990), in contrast, reported that populations of L. monocytogenes on unwashed, shredded lettuce were essentially unchanged throughout 15 days of storage at 5°C. Other researchers have reported that L. monocytogenes grows at refrigeration temperature on fresh-cut vegetables (Garcia-Gimeno and Zurera-Cosano 1997;Farber et al 1998), endive (Carlin et al 1996) and shredded cabbage (Kallander et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Beuchat and Brackett (1990), in contrast, reported that populations of L. monocytogenes on unwashed, shredded lettuce were essentially unchanged throughout 15 days of storage at 5°C. Other researchers have reported that L. monocytogenes grows at refrigeration temperature on fresh-cut vegetables (Garcia-Gimeno and Zurera-Cosano 1997;Farber et al 1998), endive (Carlin et al 1996) and shredded cabbage (Kallander et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of this organism to grow in a freshcut produce environment, including cabbage, has been well documented (4,8,10,16,25). We used a differential display method that compared the transcription of L. monocytogenes in two different environments: growth on plant tissue and growth in minimal medium.…”
Section: Discussionmentioning
confidence: 99%
“…Farber et al, 1998;Aureli et al 2000;Farber et al, 2000;Pingulkar et al, 2001). Figure 2 presents the empirical histogram of the 287 calculated TTE.…”
Section: Evaluation Of Sanitary Consequencesmentioning
confidence: 99%